Pathways to recovery and loss of nephrons in Anti-Thy-1 nephritis - Kriz, Wilhelm; Hähnel, Brunhilde; Hosser, Hiltraud; Ostendorf, Tammo; Gaertner, Soeren; Kränzlin, Bettina; Gretz, Norbert; Shimizu, Fujio; Floege, Jürgen (Journal of the American Society of Nephrology, 2003)
ABSTRACT. The present histopathologic study of anti-Thy-1.1 models of mesangioproliferative glomerulonephritis in rats provides a structural analysis of damage development and of pathways to recovery and to nephron loss. As long as the disease remains confined to the endocapillary compartment, the damage may be resolved or recover with a mesangial scar. Irreversible lesions with loss of nephrons emerge from extracapillary processes with crucial involvement of podocytes, leading to tuft adhesions to Bowman‘s capsule (BC) and subsequent crescent formation. Two mechanisms appeared to be responsible: (1) Epithelial cell proliferation at BC and the urinary orifice and (2) misdirected filtration and filtrate spreading on the outer aspect of the nephron. Both may lead to obstruction of the tubule, disconnection from the glomerulus, and subsequent degeneration of the entire nephron. No evidence emerged to suggest that the kind of focal interstitial proliferation associated with the degeneration of injured nephrons was harmful to a neighboring healthy nephron. E-mail: wilhelm.krizurz.uni-heidelberg.de